Facile fabrication of self-shrinkable AIE supramolecular gels based on benzophenone salicylaldehyde hydrazine derivatives. Issue 39 (24th September 2020) - Ma, Yao; Li, Baoxi; Zhang, Kexin; Wan, Qing; Džolić, Zoran; Wang, Zhiming; Tang, Ben Zhong
Abstract : A novel molecular design strategy to give self-shrinkable AIE-active supramolecular gels with a variation in the morphology and an obvious emission enhancement via benzophenone salicylaldehyde hydrazine (BSH) derivatives was reported. Abstract : The study of shrinkage behavior in supramolecular soft materials via the variation of shape and volume can contribute to a better understanding of and the mimicking of motions that occur in diverse organisms. The fabrication of self-shrinkable supramolecular gels is of great significance in actively moving systems but is still a big challenge. Aggregation-induced emission (AIE) has been an extremely hot topic and is believed to have significantly stimulated the development of luminescent supramolecular materials. Its realization in self-shrinkable materials can both provoke academic interest and widen the number of innovative applications for actively moving systems. Herein, we proposed a novel molecular design strategy to give self-shrinkable AIE supramolecular gels via the use of three benzophenone salicylaldehyde hydrazine derivatives substituted with different length alkyl chains. These gelator molecules prefer to adopt a twisted conformation in the monomolecular and assembled state which is beneficial to their AIE behaviors. The gels of these molecules exhibit distinct phase behaviors where those with longer alkyl chains result in the self-shrinkage of the gel. We consider that this is due to the enhancement of the mobility of the packing layers and thus a shorter inter-layer distance that leads to tighter stacking. The self-shrinkage process was concomitant with a variation in the morphology from a macroporous honeycomb structure to a more aligned and regular nanofibrous structure with an accompanying emission enhancement.